Prototypeneffekte im Grenzbereich von Phonologie und Morphologie - Elsen, Hilke (Linguistik Online, 2009)
This article presents names in science fiction and fantasy stories with problematic morphological structures as well as manufactured names which produce sound symbolic effects. The examples show a continuum from sound shape to recurring groups of sounds to morphemes. Not only individual phonemes, but also gestalts seem to constitute a level in language processing. Psychologically oriented approaches, e.g. prototype theory, deal with exactly these problems, structured categories, good and bad examples as well as continua between categories, even sound symbolism. They try to find systematicity where traditional linguistic approaches fail.